Numerical Simulation of a Moored Wave-Buoy in Waves and Current by Smoothed Particle Hydrodynamics - Capasso, Salvatore; Tagliafierro, Bonaventura; González-Ávalos, Raúl; Martínez-Estévez, Iván; Domínguez, José Manuel; Altomare, Corrado; Crespo, Alejandro J. C.; Viccione, Giacomo (Volume 7: CFD & FSI, 2023)
The behavior, safety and survivability of offshore moored systems is determined by the environmental conditions, which, along with the wave characteristics, usually include the presence of currents. Their effect modifies the wave pattern and the overall fluid behavior, and may cause inaccuracies in the estimated sea state parameters, which would eventually jeopardize the design of offshore structures. The present work provides the validation of the interaction of a moored floating sphere with the joint action of waves and current by means of the Smoothed Particle Hydrodynamics (SPH) method. An experimental campaign is carried out in a combined wave-current test tank to assess the dynamic behavior of the moored spherical buoy; the experimental data are eventually used to validate a newly developed wave-current flume in the SPH-based solver DualSPHysics. For this purpose, open boundary conditions are implemented to reproduce the fluid flow perceived by the buoy: third order wave-current theoretical flow velocity field and free surface are derived from Stokes wave theory and imposed at the inlet boundary. Thanks to the coupling with MoorDyn+, which solves the mechanics of anchoring systems, DualSPHysics is able to capture the flow-induced moored buoy motion. The results of this preliminary investigation show the feasibility of this approach for simulating moored structure subject to the joint action of waves and current. A useful and practical application for the numerical framework here developed is the high-fidelity simulation of Wave Energy Converters (WECs), for which the action of current could play a significant role in term of loads, motions and power output.